Marie Curie Training Site Scholarship - Keivanidis, Panagiotis E. (My University, 2026)
Scholarship received by project 'Analytical Methods in the Development of Polymer materials' (AMID), Marie Curie Training Site, project HPMT-CT-2000-00015 at the Max Planck Institute for Polymer Research, Mainz (DE)
Keywords: Natural sciences